Relationship between Malnutrition and the Number of Permanent Teeth in Filipino 10- to 13-Year-Olds. (29th August 2013) - Heinrich-Weltzien, Roswitha; Zorn, Carsten; Monse, Bella; Kromeyer-Hauschild, Katrin
Abstract : In the present study, we determined whether there is a delay in the eruption of permanent teeth (PT) among Filipino adolescents with stunting or thinness. Height, weight, and number of PT were recorded in 1554 Filipino 10- to 13-year-olds (711 boys; 843 girls). z -scores for height (HAZ) and body mass index (BMI) were calculated according to the WHO growth reference, and their correlations to the number of PT were assessed. 54.9% of the children have at least one form of malnutrition. Significantly, more boys (22.9%) than girls (16.5%) were thin, while no sex difference in stunting was noted (boys 48.5%; girls 44.0%). The number of PT was significantly correlated to HAZ and BMI- z -score. Stunted and thin students had significantly fewer PT than their nonaffected peers. These differences tended to be the result of delay in tooth eruption in thin and stunted adolescents. In 13-year-old girls, all PT were erupted regardless of their nutritional status indicating a catch-up. Thin and stunted boys had one tooth less than normal boys at this age. Impaired physical growth and dental development seem to have common risk factors. Therefore, regular monitoring of growth and dental development might be helpful for targeting support programmes in developing countries.